WebQual Method for Analyzing the Service Quality of the Hospital Complaint Website on User Satisfaction - Suhendra, Asep Dony; Mustomi, Dede; Supriatin, Supriatin; Ulum, Khoirul (Universitas Pendidikan Muhammadiyah (UNIMUDA) Sorong, 2024)
The Hospital Complaints Website acts as a forum for the public to convey complaints, aspirations, and complaints regarding hospital performance, so the importance of the quality of service on this website cannot be ignored. Researchers are interested in conducting a more comprehensive study regarding the quality of hospital complaint websites. The research aims to measure the quality of service on the hospital complaints website by paying attention to several aspects of the user and looking for obstacles found on the Hospital Complaints website. The data collection method involves the acquisition of primary research data using the WebQual method as the main conceptual framework for analyzing the quality of services contained in the Hospital Complaints website which emphasizes assessing the quality of satisfaction with using the website which consists of four variables: usability quality, information quality, service interaction quality, and user satisfaction, while secondary data research carried out questionnaires and interviews with staff, patients and hospital leaders as many as 41 respondents to obtain quantitative data. To obtain quantitative data, the researcher compiled a series of valid research instruments that describe the relationship between several research dimensions in the WebQual method, including 4 variables and 26 questions. The data collected will be the basis for solving the problem that is the focus of the research and testing the hypothesis that has been formulated. Previously. Based on the results of validation testing, the r counting variable consists of Quality of Use = 0.936, Quality of Information = 0.859, Quality of Service Interaction = 0.874 against the r table of satisfaction with use 0.260, where (r count > r table) is declared valid, analysis of reliability test data value Information Value Criteria Cronbach's Alpha, Usability Quality 0.909 > 0.60, Information Quality 0.919 > 0.60, Service Interaction Quality 0.854 > 0.60, User Satisfaction 0.868 > 0.60. This means that each of these variables influences user satisfaction.